Riding Others’ Coattails: Low self-control individuals value self-control in others - Shea, Catherine T. (Psychol Sci, 2013)
Two laboratory experiments and one dyadic study of ongoing romantic partners examine how temporary and chronic deficits in self-control affect evaluations of others. We suggest that when individuals lack self-control resources, they value such resources in others. Supporting this hypothesis, we find that low (but not high) self-control individuals use self-control information when judging others, evaluating others with high self-control more positively than others with low self-control. In Study 1, depleted participants preferred higher (vs. lower) self-control others; control participants did not show this preference. Study 2 conceptually replicated this effect using a behavioral measure of trait self-control. In Study 3, low (but not high) self-control individuals reported greater dependence on ongoing dating partners with high (vs. low) self-control. We theorize that low self-control individuals may use interpersonal relationships to compensate for their lack of personal self-control resources.